(untitled) (Applied Biological Research, 2016)
Constant or transitory high temperatures affect plant growth and development inducing diverse morphological and physiological changes in plants which ultimately causes yield decrease. The traits like relative injury (RI%), chlorophyll content, canopy temperature depression (CTD), heat susceptibility index (HSI), 1000-kernel weight (TKW), grain filling duration (GFD) were used in present study to assess the capability of plants to tolerate heat stress. The study revealed that the evaluated wheat genotypes showed variable degree of tolerance against heat fordifferent traits. On the basis of morpho-physiological traits such as RI, chlorophyll content at 15 days after anthesis (DAA), CTD at 15 DAA, HSI, TKW, GFD, genotypes HD2329 x HD2967 (19.2%), WH1021 (-21.7%), JOB666 X WH1105 (-37.5%), WH1124 X HD2967 (0.55), HD2891 (2.1%) and WAXWING X HD2967 (-2.15%) were identified as the most heat tolerant genotypes for respective characters. For grain yield out of 54 wheat genotypes, DBW90, HD2329, UP2843 × HD2967, WH1124 × HD3059, WH1124 × HD2967, MACS6272 × WH1105, MACS6272 × HD2967, HD2891 × WH1105 and UP2338 were classified as heat tolerant.